(untitled) (Jurnal Peternakan Lingkungan Tropis, 2021)
The most common ruminants kept by the people of Samarinda are the Ettawa Peranakan (PE) goat. The Ettawa Peranakan Goat (PE) is one of the local goats that is well knowen in Indonesia, one of whichis in East Kalimantan. Body weight is one measure of livestock productivity, body weight can be used as a new selection of seeds. This study aims to determine the diversity of Ettawa cross-breed (PE) goat identities in collecting traders, to see the status of feamale Ettawa cross-breed (PE) goats in collecting traders in Samarinda city. The data used in this research are primary data. Primary data is obtained directly from direct interviews with owners and by conducting field observations. The collection of data used in the study, namely: Bust, Length, Shoulder Height ang Weight. Using the side purposive method, determining, the area of East Kalimantan, there is a population of ettawa peranakan goats. Determining the research location in the city of Samarinda, variables, use in this study are the main variables in and the supporting variables. The analisysis used in this research is qualitative an quantitative analysisi, descriptive analysis and regression equation analysis. The results showed that the first msting age was 11.17±1.37 months, the average service per conception was 1.0±0.50 months, and pos partum was 1.78±0.45 months. The mean an standard deviations values of circumference were 75.16 ±6.74, body 69.63±7.01, shoulder height 71.69±5.97, and body weight 38.6±7.67 kg. Based on the Analysis of the data obtained from the research results, it can be concluded that: Phenotypc diversity of female Ettawa (PE) crossbred goats in Northa Samarinda and Samarinda Ulu has diversity coefficient values of diversity, namely shoulder height, body length, and chest circumference had the coefficient of variability, respectively, namely 71%, 78% and 79%.